2019
DOI: 10.2460/javma.255.4.446
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Health Belief Model to identify factors associated with owner adherence to elimination diet trial recommendations in dogs

Abstract: OBJECTIVE To use the Health Belief Model to identify factors associated with owner adherence to elimination diet trial (EDT) recommendations by veterinarians for dogs with suspected cutaneous adverse food reactions (CAFRs). SAMPLE 192 owners of dogs prescribed an EDT between April 1, 2012, and April 1, 2017. PROCEDURES Owners of dogs prescribed an EDT to diagnose CAFRs were identified through review of medical records from a single veterinary dermatology specialty practice. Identified owners were invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Our findings show that urgency to seek care for chronic conditions is driven primarily by the strength of relationship with a dog and HBM constructs. Previous studies utilized the HBM in exploring factors related to seeking healthcare focused primarily on seeking vaccinations and preventative care (33,34,74). Our study shows that HBM constructs are useful in predicting healthcare seeking for chronic health issues.…”
Section: Using Health Belief Model To Predict Intentions and Urgency ...mentioning
confidence: 69%
See 1 more Smart Citation
“…Our findings show that urgency to seek care for chronic conditions is driven primarily by the strength of relationship with a dog and HBM constructs. Previous studies utilized the HBM in exploring factors related to seeking healthcare focused primarily on seeking vaccinations and preventative care (33,34,74). Our study shows that HBM constructs are useful in predicting healthcare seeking for chronic health issues.…”
Section: Using Health Belief Model To Predict Intentions and Urgency ...mentioning
confidence: 69%
“…Strong associations between the behavior of seeking care and score on the urgency to seek care shows that owners who report high urgency on hypothetical scenarios likely apply a similar rule when deciding if their dog needs to seek care in real life. Self-efficacy to seek care was identified as an important predictor of seeking veterinary care in other contexts, such as adherence to elimination diet trial (74), showing that improving dog owners' health literacy, i.e., dog owner's ability to seek, evaluate, and apply knowledge regarding dog health, could increase their engagement with veterinary care. Changes in how care was delivered and difficulties in accessing care for nonemergency conditions identified in the qualitative analysis could lead owners of dogs with chronic health conditions to delay seeking care, reflected here.…”
Section: Using Health Belief Model To Predict Intentions and Urgency ...mentioning
confidence: 99%
“…Although there is a relative scarcity of similar studies within veterinary medicine, some have investigated the differences in patterns of adherence to immunotherapy. 15,16,18 The human medical field has long recognized the need to scrutinize clinician and patient factors in order to smooth out the referral process and make certain therapies more readily available to patients. [12][13][14][19][20][21][22][23] Findings from studies such as these have been used to improve the specialist-generalist relationship, provide better continuity of care and ensure better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…13 Physicians have long recognized the need to investigate perceived barriers to referral and specialized treatment which can include specialty services with restricted provider networks, inconvenient office hours, and difficulty in getting an appointment quickly. [14][15][16] To the best of the authors' knowledge, specific factors impacting referral to specialized veterinary medicine have not been evaluated in the veterinary dermatology subset. The objective of this pilot survey study was to establish the presence of and further characterize specific factors which could impact primary veterinarians' decisions to consider specialty referral or to offer allergen-specific testing and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Given that there are no reliable diagnostic tests to confirm AFRs in dogs and cats, the only way to establish a diagnosis is to perform a strict diet trial. In one study, it was reported that only 40 per cent of 192 pet owners followed an elimination diet trial with 100 per cent adherence (Painter and others 2019). For this reason, it is vital that pet owners are well informed and motivated to perform these trials.…”
Section: Diagnosismentioning
confidence: 99%